Interfacial Chemistry Triggers Ultrafast Radiative Recombination in Metal Halide Perovskites. Issue 13 (7th February 2022) - Dong, Haiyun; Zhang, Chunhuan; Nie, Weijie; Duan, Shengkai; Saggau, Christian N.; Tang, Min; Zhu, Minshen; Zhao, Yong Sheng; Ma, Libo; Schmidt, Oliver G.
Abstract: Efficient radiative recombination is essential for perovskite luminescence, but the intrinsic radiative recombination rate as a basic material property is challenging to tailor. Here we report an interfacial chemistry strategy to dramatically increase the radiative recombination rate of perovskites. By coating aluminum oxide on the lead halide perovskite, lead–oxygen bonds are formed at the perovskite‐oxide interface, producing the perovskite surface states with a large exciton binding energy and a high localized density of electronic state. The oxide‐bonded perovskite exhibits a ≈500 fold enhanced photoluminescence with a ≈10 fold reduced lifetime, indicating an unprecedented ≈5000 fold increase in the radiative recombination rate. The enormously enhanced radiative recombination promises to significantly promote the perovskite optoelectronic performance. Abstract : An interfacial chemistry strategy is developed to dramatically increase radiative recombination of perovskites. The oxide‐bonded perovskite has a large exciton binding energy and a high localized density of electronic state, exhibiting an unprecedented 5000 fold increase in the radiative recombination rate. The enormously enhanced radiative recombination promises to significantly promote the perovskite optoelectronic performance.